THE CONTENT OF IMPROVING THE PROFESSIONAL TRAINING OF STUDENTS ON THE BASIS OF A DIFFERENTIATED APPROACH - Chorshanbiyev Zafar Esanpulatovich (American Journals, 2024)
The points presented in the article are a combination of ideas about the mechanisms for the development and implementation of the e-learning environment model, which makes it possible to improve the professional training of future engineers studying at a technical higher educational institution on the basis of a differentiated approach.
Keywords: Ingenuity, differentiated approach, SWOT Analysis, forum, problem situation, online chat, interesting modeling, Creative Lab, intellectual puzzle, cognitive-functional.